2013
DOI: 10.3233/tad-130380
|View full text |Cite
|
Sign up to set email alerts
|

Everyday technologies' levels of difficulty when used by older adults with and without cognitive impairment – Comparison of self-perceived versus observed difficulty estimates

Abstract: BACKGROUND: Older adults may have difficulties in using everyday technologies, ET, e.g. micros, computers, particularly those with cognitive impairment. To guide supportive interventions, more knowledge of how to best assess ET use is needed. OBJECTIVE: To provide new knowledge of perceived and observed levels of difficulty of ETs in older adults with and without cognitive impairment. METHODS: Two samples of older adults (n = 118 and 116) with and without cognitive impairment were assessed. One was interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In agreement with earlier suggestions, we propose that information regarding perceived difficulties in combination with observation of actual ability will offer an understanding of a client's strengths and limitations in occupational performance and of their own perception and awareness of their ability (12,(38)(39)(40)(41)(42). However, even if the use of both self-reports and observations is underscored in guidelines for client-centred occupation-based intervention processes (12) as well as in research of the group (39), there can exist a discrepancy to clinical practice.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with earlier suggestions, we propose that information regarding perceived difficulties in combination with observation of actual ability will offer an understanding of a client's strengths and limitations in occupational performance and of their own perception and awareness of their ability (12,(38)(39)(40)(41)(42). However, even if the use of both self-reports and observations is underscored in guidelines for client-centred occupation-based intervention processes (12) as well as in research of the group (39), there can exist a discrepancy to clinical practice.…”
Section: Discussionsupporting
confidence: 83%
“…The generated hierarchy displaying the ETs on a continuum from less to more challenging to use (Table 3) reaffirms earlier knowledge of domestic ETs as generally being easier to use (Patomella et al ., 2011; Malinowsky et al ., 2013) because all but one ET within home maintenance were found among the “relatively more easy” ETs. Somewhat unexpectedly, a larger proportion of ETs classified as “relatively more easy” to use at baseline became significantly more challenging to use at year five (17%) compared to the proportion of ETs with significant DIF that at baseline were classified as “relatively more challenging” (13%).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, complexity in process might be the common denominator challenging both cognition and ET use. Cross-sectional research has suggested that domestic ETs such as coffee makers, stoves, and microwave ovens are generally perceived and observed to be easier to use, while information and communication technologies (ICT) like cell phones and computers are more challenging (Patomella et al ., 2011; Malinowsky et al ., 2013). However, longitudinal studies examining how the perceived challenge of specific ETs develops in persons with cognitive decline are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our research has shown that technology also may be a hindrance in these people's everyday lives and repeated studies have shown that people with more severe cognitive impairment have more difficulties to use technology than those with mild impairment, good recovery or no known cognitive impairment [12][13][14][15]. In a few studies, the challenge levels of common everyday technologies have also been investigated in samples with and without dementia or MCI [2,[16][17][18][19] and samples with ABI [5]. Even though research has shown that people's perceptions of a technology's level of difficulty is related to the severity of cognitive decline, we do not yet know if people with different cognitively disabling diagnoses perceive everyday technologies to be similarly easy or challenging, or if it varies across diagnoses.…”
Section: Introductionmentioning
confidence: 94%
“…The use of technological artefacts and services such as mobile phones, internet banking and automatic ticket machines is increasing in homes as well as in public life and societal services. A huge variety of everyday technological (ET) artefacts and services, both digital and traditional non-digital technology, are currently in use in large populations internationally, and new technologies are continuously developed to further facilitate our lives, e.g., to promote inclusion and effective use of time, and also to compensate for disabilities [1,2]. Accordingly, the ability to manage everyday technology has become increasingly important for participation in everyday activities at home and in the community [1,3,4].…”
Section: Introductionmentioning
confidence: 99%